2023
DOI: 10.31729/jnma.8060
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Induced Hypertensive Disorders among Patients Admitted to the Department of Obstetric and Gynecology in a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Hypertensive disorder of pregnancy is among the leading causes of maternal and perinatal mortality in developing countries. There are only few studies regarding this topic so this study helps us to improve our management protocol thereby reducing maternal and foetal morbidity and mortality. The aim of this study was to find out the prevalence of pregnancy induced hypertensive disorder among patient admitted to the Department of Obstertric and Gynecology in a tertiary care centre. Methods: A descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the era of the contemporary epidemic of caesarean sections and increased availability of drugs used in postpartum atony, PAS may become the dominant indication for postpartum hysterectomy and replace uterine atony in countries with high CSP rates [13]. Studies conducted on cohorts of patients in some countries have shown an increasing trend in the occurrence of this form of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of the contemporary epidemic of caesarean sections and increased availability of drugs used in postpartum atony, PAS may become the dominant indication for postpartum hysterectomy and replace uterine atony in countries with high CSP rates [13]. Studies conducted on cohorts of patients in some countries have shown an increasing trend in the occurrence of this form of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, most maternal deaths due to hypertensive disorders occur in girls younger than 20 years, compared to the total estimated population of women. 3 , 5 This could be attributable to a lack of knowledge or ignorance about the subject among adolescents and young women. Unintended pregnancies are common (41.9%) among adolescent girls and young women in South Africa, with almost all of these (26.3%) ending in abortions; 13 this may explain the higher prevalence of HIP in this population in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Not only does it contribute to the latter, but is also associated with prolonged chronic hypertension, renal failure, or neurological disorders, which may, in turn, contribute to most pregnancy-related health complications. [3][4][5] Research has established maternal mortality and morbidity as the worse health issue on a universal scale. Global estimations demonstrate that 287 000 women died from a maternal cause during 2020, which equates to about 800 maternal deaths per day.…”
Section: Introductionmentioning
confidence: 99%